ANALISIS KESESUAIAN HABITAT MANGROVE PADA KAWASAN MANGROVE BUATAN DI BAROS, BANTUL, DAERAH ISTIMEWA YOGYAKARTA - , NANANG SETIAWAN, Ni Putu Diana Mahayani, S.Hut., M.For. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Mangroves require particular habitat characteristics to grow well such as substrate, level of water salinity, temperature, pH, dissolved oxygen. The mangrove area of Baros is located in Opak estuarine which has specific hydrologic conditions which affect the mangrove habitat condition at the downstream, due to is coarse materials carried such as sand from Merapi Volcano. This study aims to identify (1) the physical-chemical conditions of mangrove vegetation habitat Baros, (2) the structure and composition of Baros mangrove, and (3) the mangrove habitat suitability based on comparations of the aquatic physical-chemical, vegetation structure and composition betwen Baros with Pemalang rehabilitation of mangrove and the mangrove natural forests on Marosi and Air Saga. The area was grouped into four blocks which three blocks represent areas with mangrove plants and one block represents the natural habitat condition before plantation. Four plots of 5x5 m were established in each block along the river banks. The physical-chemical aquatic parameters were measured such as temperature, pH, salinity, dissolved oxygen, mud thickness, organic matter content and substrate texture. The vegetation structure and composition were also observed such as the number of species, DBH, height of the mangrove trees. The habitat parameters observed was then analysed statiscically using hypothesis comparation test. The results showed that temperature and pH parameters were appropriate the water quality standards that is allowed for the mangrove growth